Laminate, method for producing laminate, polarizing plate, and method for producing polarizing plate

By forming an easy adhesive layer on the surface of the polyester resin base and forming a polyvinyl alcohol resin layer thereon, the problem of insufficient adhesion between the polyester resin base and the polarizing mirror is solved, and the adhesion and performance of the polarizer are improved.

CN119846761APending Publication Date: 2025-04-18NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510046530.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-06-13
Filing Date
2018-06-07
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, the adhesion between the polyester resin substrate and the polarizing mirror is insufficient, resulting in poor performance of the polarizer.

Method used

The adhesion between the two is improved by forming an easy-adhesive layer on the surface of the polyester resin base material and forming a polyvinyl alcohol resin layer on the surface of the easy-adhesive layer. The water contact angle of the easy-to-adhesive layer is above 70° just after adding water drops, and is reduced by more than 2° after 30 seconds after adding drip.

Benefits of technology

The polyester resin base material and the polyvinyl alcohol resin layer have excellent adhesion and properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119846761A_ABST
    Figure CN119846761A_ABST
Patent Text Reader

Abstract

Provided is a laminate having excellent adhesion between a polyester-based resin substrate and a polyvinyl alcohol-based resin layer. The laminate has a polyester-based resin substrate having a highly adhesive layer formed on the surface thereof, and a polyvinyl alcohol-based resin layer laminated on the polyester-based resin substrate with the highly adhesive layer interposed therebetween, and the water contact angle of the highly adhesive layer is 70 DEG or more immediately after water is added to the highly adhesive layer, and is reduced by 2 DEG or more 30 seconds after the water is added.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application filed on June 7, 2018, with application number 201880039559.1 and invention name “Laminate, method for manufacturing a laminate, polarizer, and method for manufacturing a polarizer”. Technical Field

[0002] The present invention relates to a laminate, a method for manufacturing the laminate, a polarizing plate, and a method for manufacturing the polarizing plate. Background Art

[0003] A method for producing a thin polarizer by forming a polyvinyl alcohol resin layer on a polyester resin substrate and stretching and dyeing the laminate has been proposed (for example, Patent Document 1). Such a method for producing a polarizer has attracted attention as being able to contribute to, for example, thinning of image display devices.

[0004] The polyester resin substrate can be used as a protective layer of a polarizer without peeling it off. Therefore, the laminate of the polyester resin substrate and the polarizer can be directly used as a polarizing plate without laminating a protective film on the polarizer, which can contribute to the cost reduction of image display devices, for example.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2000-338329 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, the laminate of the polyester resin substrate and the polarizer, that is, the polarizing plate, produced by the above method may have insufficient adhesion between the polyester resin substrate and the polarizer.

[0010] The present invention is made to solve the above-mentioned existing problems, and its main purpose is to provide a laminate with excellent adhesion between a polyester resin substrate and a polyvinyl alcohol resin layer, a method for producing such a laminate, a polarizing plate with excellent adhesion between a polyester resin substrate and a polarizer, and a method for producing such a polarizing plate.

[0011] Solutions to the problem

[0012] The laminate of the present invention comprises: a polyester resin substrate having an easy-adhesive layer formed on the surface, and a polyvinyl alcohol resin layer laminated on the polyester resin substrate via the easy-adhesive layer, wherein the water contact angle of the easy-adhesive layer is greater than 70° just after water is dropped onto the easy-adhesive layer, and decreases by more than 2° after 30 seconds from the dropping.

[0013] In one embodiment, the easy-adhesion layer contains a polyvinyl alcohol-based component and a polyolefin-based component.

[0014] In one embodiment, the mixing ratio of the polyvinyl alcohol component to the polyolefin component is 10:90 to 50:50.

[0015] According to another aspect of the present invention, a method for manufacturing a laminate is provided. The method for manufacturing a laminate comprises: forming an easy-adhesion layer on the surface of a polyester resin substrate; and forming a polyvinyl alcohol resin layer on the surface of the easy-adhesion layer, wherein the water contact angle of the easy-adhesion layer is 70° or more immediately after water is dropped onto the easy-adhesion layer, and decreases by 2° or more after 30 seconds from the drop.

[0016] According to another aspect of the present invention, a method for manufacturing a polarizing plate is provided, wherein the method comprises dyeing and stretching the laminated body to form the polyvinyl alcohol-based resin layer into a polarizer.

[0017] According to another aspect of the present invention, a polarizing plate is provided. The polarizing plate comprises: a polyester resin substrate having an easy-adhesion layer formed on the surface, and a polarizer laminated on the polyester resin substrate via the easy-adhesion layer, wherein the thickness of the polarizer is 10 μm or less, and the water contact angle of the easy-adhesion layer is 70° or more immediately after water is dropped onto the easy-adhesion layer, and decreases by 2° or more after 30 seconds from the drop.

[0018] Effects of the Invention

[0019] According to the present invention, by using an easy-adhesion layer whose water contact angle is 70° or more immediately after water is dropped and decreases by more than 2° after 30 seconds from the drop, a laminate having excellent adhesion between a polyester resin substrate and a polyvinyl alcohol resin layer, a method for producing such a laminate, and a polarizing plate having excellent adhesion between a polyester resin substrate and a polarizer can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention.

[0021] Explanation of symbols

[0022] 10Polyester resin base material

[0023] 20 Easy bonding layer

[0024] 30 Polyvinyl alcohol resin layer

[0025] 100 layers DETAILED DESCRIPTION

[0026] Embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.

[0027] A. Laminated body

[0028] Figure 1 It is a schematic cross-sectional view of a laminate of one embodiment of the present invention. The laminate 100 comprises: a polyester resin substrate 10 having an easy-adhesive layer 20 formed on the surface, and a polyvinyl alcohol (PVA) resin layer 30 laminated on the polyester resin substrate 10 via the easy-adhesive layer 20. The water contact angle of the easy-adhesive layer 20 is 70° or more just after water is dropped onto the easy-adhesive layer 20, and decreases by more than 2° after 30 seconds from the drop. The time-dependent change (reduction) of the above-mentioned water contact angle can be obtained by measuring the water contact angle (θ1) just after water is dropped onto the easy-adhesive layer, and the water contact angle (θ2) 30 seconds after the drop, and subtracting θ1 from θ2. The water contact angle just after water is dropped onto the easy-adhesive layer is typically the water contact angle measured 1 second after the drop. In one embodiment, the easy-adhesive layer 20 contains a polyvinyl alcohol component and a polyolefin component. At this time, the mixing ratio of the polyvinyl alcohol component to the polyolefin component is preferably 10:90 to 50:50. Thus, a laminate having excellent adhesion between the polyester resin substrate and the PVA resin layer can be obtained. In one embodiment, the laminate can be used to make a polarizer. The method for making a polarizer is described later in item D, which includes: dyeing and stretching the laminate, thereby making the PVA resin layer into a polarizer.

[0029] A-1. Polyester resin substrate

[0030] As the forming material of the polyester resin substrate, for example, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), isophthalic acid, copolymerized PET (PET-G) containing alicyclic dicarboxylic acids or alicyclic diols containing cyclohexane rings, and other polyesters, as well as their copolymers, mixtures, etc. can be used. Among them, it is preferred to use amorphous (uncrystallized) PET or copolymerized PET. According to these resins, they are amorphous in the unstretched state and have excellent stretchability suitable for high-ratio stretching, and are crystallized by stretching and heating, thereby imparting heat resistance and dimensional stability. In addition, heat resistance to the extent that the PVA resin can be applied and dried in the unstretched state can be ensured.

[0031] The glass transition temperature (Tg) of the polyester resin substrate is preferably 170°C or less. By using such a polyester resin substrate, the stretchability can be fully ensured while suppressing the crystallization of the PVA resin layer. Considering the viewpoints of plasticizing the polyester resin substrate with water and stretching in an aqueous solution well, it is more preferably 120°C or less. In one embodiment, the glass transition temperature of the polyester resin substrate is preferably 60°C or more. By using such a polyester resin substrate, when applying and drying a coating solution containing the PVA resin described later, the polyester resin substrate can be prevented from deforming (for example, unevenness, relaxation, wrinkles, etc.). In addition, the laminate can be well stretched at an appropriate temperature (for example, about 60°C to 70°C). In another embodiment, when applying and drying a coating solution containing a PVA resin, the glass transition temperature can also be lower than 60°C as long as the polyester resin substrate does not deform. In addition, the glass transition temperature (Tg) is a value obtained in accordance with JIS K 7121.

[0032] In one embodiment, the water absorption of the polyester resin substrate is preferably 0.2% or more, more preferably 0.3% or more. Such a polyester resin substrate absorbs water, and water can play the role of a plasticizer for plasticization. As a result, the tensile stress can be greatly reduced during stretching in an aqueous solution, and excellent stretchability is obtained. On the other hand, the water absorption of the polyester resin substrate is preferably 3.0% or less, more preferably 1.0% or less. By using such a polyester resin substrate, undesirable situations such as a significant decrease in the dimensional stability of the polyester resin substrate during manufacturing and deterioration in the appearance of the resulting laminate can be prevented. In addition, it can prevent the situation where the PVA resin layer is broken during stretching in an aqueous solution or peeled off from the polyester resin substrate. In addition, the water absorption is a value obtained according to JIS K 7209.

[0033] The thickness of the polyester resin substrate is preferably 20 μm to 300 μm, more preferably 30 μm to 200 μm.

[0034] The surface of the polyester resin substrate may be subjected to a surface modification treatment (such as a corona treatment) in advance. Adhesion can be further improved by such treatment.

[0035] A-2. Easy-adhesion layer

[0036] As mentioned above, the water contact angle of the easy bonding layer is more than 70° after just dripping water, and is reduced by more than 2° after 30 seconds after dripping. Just after dripping water, the water contact angle of the easy bonding layer is preferably 75°~85°. The time-dependent change of the water contact angle occurring after 30 seconds after dripping is preferably -2° (reduced by 2°)~-5° (reduced by 5°). The water contact angle of the easy bonding layer after just dripping water is more than 70°, and the time-dependent change (reduction) of the water contact angle occurring after 30 seconds after dripping is more than 2°, so that when a PVA-type resin layer can be formed on the easy bonding layer, the easy bonding layer can be dissolved into the PVA-type resin layer with a composition. Specifically, by making the above-mentioned water contact angle change over time to -2°~-5°, when a coating layer of a PVA-type resin is formed on the easy bonding layer, about 10% by volume~34% by volume of the easy bonding layer can be dissolved into the coating layer of the PVA-type resin. Thereby, the adhesion between the polyester-based resin substrate and the PVA-based resin layer can be improved.

[0037] Easy bonding layer can be a layer substantially only formed by the easy bonding layer forming composition described later, or can be a layer or region formed by mixing (including compatibility) the easy bonding layer forming composition with the PVA type resin layer described later. By being formed with an easy bonding layer, excellent adhesion can be obtained. The thickness of the easy bonding layer is preferably 500nm~3000nm, more preferably 800nm~2000nm. If the thickness of the easy bonding layer is too thin, there is a worry that sufficient adhesion cannot be obtained. On the other hand, if the thickness of the easy bonding layer is too thick, then when forming the PVA type resin coating layer described later, there will be a generation of depression, the coating film obtained will produce uneven undesirable conditions, there is a worry that is difficult to obtain the laminated body with excellent appearance, the easy bonding layer in this case can be confirmed by observing the cross section of the laminated body with a scanning electron microscope (SEM).

[0038] The easy-adhesion layer preferably contains a polyvinyl alcohol component and a polyolefin component. By making it into such a composition, the water contact angle of the easy-adhesion layer and the time-varying change of the water contact angle can be made into an angle within the above-mentioned range, and as a result, a laminate with excellent adhesion of a polyester resin substrate and a PVA resin layer can be obtained. And, by dyeing and stretching the above-mentioned laminate, a polarizer with excellent adhesion of a polyester resin substrate and a polarizer can be obtained. The polyvinyl alcohol component can use any appropriate PVA resin. Specifically, polyvinyl alcohol and modified polyvinyl alcohol can be cited. Modified polyvinyl alcohol, for example, can be cited as polyvinyl alcohol modified with acetoacetyl, carboxylic acid, acryloyl and / or carbamate. Among these, acetoacetyl modified PVA is preferably used. As acetoacetyl modified PVA, a polymer having at least a repeating unit shown in the following general formula (I) is preferably used.

[0039] [Chemical formula 1]

[0040]

[0041] In the above formula (I), the ratio of n to l+m+n is preferably 1% to 10%.

[0042] The average polymerization degree of the acetoacetyl-modified PVA is preferably 1000 to 10000, more preferably 1200 to 5000. The saponification degree of the acetoacetyl-modified PVA is preferably 97 mol % or more. The pH of a 4 wt % aqueous solution of the acetoacetyl-modified PVA is preferably 3.5 to 5.5. It should be noted that the average polymerization degree and saponification degree can be obtained based on JIS K 6726-1994.

[0043] The above-mentioned polyolefin component can use any appropriate polyolefin resin. As the main component of the polyolefin resin, i.e., the olefin component, for example, olefin hydrocarbons having 2 to 6 carbon atoms such as ethylene, propylene, isobutylene, 1-butene, 1-pentene, and 1-hexene can be cited. They can be used alone, or two or more can be used in combination. Among these, olefin hydrocarbons having 2 to 4 carbon atoms such as ethylene, propylene, isobutylene, and 1-butene are preferably used, and ethylene is more preferably used.

[0044] In the monomer components constituting the polyolefin-based resin, the proportion of the olefin component is preferably 50% by weight to 95% by weight.

[0045] The polyolefin resin preferably contains a carboxyl group and / or an anhydride group thereof. Such a polyolefin resin can be dispersed in water and can smoothly form an easy-adhesion layer. As monomer components having such functional groups, for example, unsaturated carboxylic acids and their anhydrides, half esters and half amides of unsaturated dicarboxylic acids can be cited. As specific examples thereof, acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, and crotonic acid can be cited.

[0046] The molecular weight of the polyolefin resin is, for example, 5,000 to 80,000.

[0047] In the easy-adhesive layer, the mixing ratio of the polyvinyl alcohol component and the polyolefin component (the former: the latter (solid content)) is preferably 10:90~50:50, and more preferably 20:80~50:50. If the polyvinyl alcohol component is too much, there is a concern that sufficient adhesion cannot be obtained. Specifically, when the PVA resin layer is peeled off from the polyester resin substrate, the required peeling force is reduced, and there is a concern that sufficient adhesion cannot be obtained. On the other hand, if the polyvinyl alcohol component is too little, there is a concern that the appearance of the obtained laminate is damaged. Specifically, when the easy-adhesive layer is formed, there is a concern that undesirable conditions such as white turbidity of the coating film occur, making it difficult to obtain a laminate with excellent appearance.

[0048] A-3. PVA-based resin layer

[0049] The PVA resin forming the above-mentioned PVA resin layer can be any appropriate resin. For example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be mentioned. Polyvinyl alcohol can be obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer can be obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree is calculated according to JIS K 6726-1994. By using a PVA resin with such a saponification degree, a polarizing film with excellent durability can be obtained. When the saponification degree is too high, there is a concern about gelation.

[0050] The average polymerization degree of the PVA-based resin can be appropriately selected according to the purpose. The average polymerization degree is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. It should be noted that the average polymerization degree can be obtained according to JIS K 6726-1994.

[0051] The thickness of the PVA-based resin layer is typically 20 μm or less, preferably 15 μm or less, and more preferably 10 μm or less. On the other hand, the thickness of the PVA-based resin layer is preferably 1.0 μm or more, and more preferably 2.0 μm or more.

[0052] B. Method for producing laminate

[0053] The laminate of the present invention can be produced by any appropriate method. In one embodiment, the laminate is produced by a method comprising the steps of: forming an easy-adhesion layer on a surface of a polyester resin substrate; and forming a PVA-based resin layer on a surface of the easy-adhesion layer.

[0054] B-1. Formation of easy-adhesion layer

[0055] The method for forming the easy-adhesion layer on the surface of the polyester resin substrate can adopt any appropriate method. Typically, the easy-adhesion layer forming composition can be applied to the surface of the polyester resin substrate and dried to form the easy-adhesion layer. In the composition for forming the easy-adhesion layer, the mixing ratio of the polyvinyl alcohol component to the polyolefin component (the former: the latter (solid content)) is preferably 10:90~50:50, and more preferably 20:80~50:50.

[0056] The composition for forming the easy bonding layer is preferably aqueous. The composition for forming the easy bonding layer may contain an organic solvent. As the organic solvent, ethanol, isopropanol, etc. can be cited. The solid content concentration of the composition for forming the easy bonding layer is preferably 1.0 wt % to 10 wt %.

[0057] The composition for forming an easy-adhesion layer may also contain additives. Examples of additives include crosslinking agents. Examples of crosslinking agents include Oxazoline, boric acid, methylol compounds such as trimethylol melamine, carbodiimide, isocyanate compounds, epoxy compounds, etc. The amount of additives in the composition for forming an easy-adhesion layer can be appropriately set according to the purpose, etc. For example, the amount of the crosslinking agent is preferably 10 parts by weight or less, more preferably 0.01 parts by weight to 10 parts by weight, and further preferably 0.1 parts by weight to 5 parts by weight, relative to 100 parts by weight of the total of the polyvinyl alcohol component and the polyolefin component.

[0058] Any appropriate method may be adopted as the coating method of the adhesive layer-forming composition, for example, roll coating, spin coating, wire bar coating, dip coating, die coating, flow coating, spray coating, knife coating (comma coating etc.) and the like.

[0059] After applying the easily adhesive layer-forming composition, the coating film may be dried at a drying temperature of, for example, 50° C. or higher.

[0060] B-2. Formation of PVA-based resin layer

[0061] As a method for forming the PVA type resin layer on the surface of the easy adhesion layer, any appropriate method may be adopted. Preferably, a coating liquid containing a PVA type resin is applied to the surface of the easy adhesion layer formed on the polyester type resin substrate and dried to form the PVA type resin layer.

[0062] The coating solution containing PVA resin is typically a solution obtained by dissolving the above-mentioned PVA resin in a solvent. As the solvent, for example, water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyols such as trimethylolpropane, amines such as ethylenediamine and diethylenetriamine can be cited. They can be used alone or in combination of two or more. Of these, water is preferred. The PVA resin concentration of the coating solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. As long as it is such a resin concentration, a uniform coating film can be formed.

[0063] Additives may also be added to the coating liquid. Examples of additives include plasticizers, surfactants, and the like. Examples of plasticizers include polyols such as ethylene glycol and glycerol. Examples of surfactants include nonionic surfactants. They can be used to further improve the uniformity, dyeability, and stretchability of the obtained PVA-based resin layer. In addition, examples of additives include easy-adhesion components. By using easy-adhesion components, the adhesion between the polyester-based resin substrate and the PVA-based resin layer can be improved. As a result, undesirable situations such as the PVA-based resin layer peeling off from the polyester-based substrate can be suppressed, thereby enabling good dyeing and stretching in aqueous solution as described later. As easy-adhesion components, modified PVAs such as acetoacetyl-modified PVAs can be used.

[0064] The coating liquid may be applied by the same method as the above-mentioned method for applying the composition for forming an easily adhesive layer. After application, the coating film may be dried. The drying temperature at this time is preferably 50° C. or higher.

[0065] Before forming the PVA-based resin layer, the easily adhesive layer may be subjected to a surface treatment (eg, corona treatment) to improve the adhesion between the polyester-based resin substrate and the PVA-based resin layer.

[0066] C. Polarizer

[0067] The polarizer of the present invention comprises a polyester resin substrate having an easy-adhesive layer formed on the surface, and a polarizer laminated on the polyester resin substrate via the easy-adhesive layer. The thickness of the polarizing film is 10 μm or less. The easy-adhesive layer is as described in the above-mentioned item A-2, and the method for forming the easy-adhesive layer is as described in the above-mentioned item B-1. Thus, a polarizer having excellent adhesion between the polyester resin substrate and the polarizer can be obtained. The polarizer can also have a protective film on the side of the polarizer opposite to the easy-adhesive layer.

[0068] C-1. Polarizer

[0069] The polarizer is essentially a PVA-based resin layer oriented by iodine adsorption. The thickness of the polarizer is less than 10 μm, preferably less than 7.5 μm, and more preferably less than 5 μm, as described above. On the other hand, the thickness of the polarizer is preferably greater than 0.5 μm, and more preferably greater than 1.5 μm. If the thickness is too thin, there is a concern that the optical properties of the resulting polarizer will be reduced. The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The monomer transmittance of the polarizer is preferably greater than 40.0%, more preferably greater than 41.0%, and further preferably greater than 42.0%. The polarization degree of the polarizer is preferably greater than 99.8%, more preferably greater than 99.9%, and further preferably greater than 99.95%.

[0070] The PVA-based resin forming the PVA-based resin layer is as described in the above-mentioned section A-3.

[0071] C-2. Protective film

[0072] As described above, the polarizing plate may have a protective film on the side of the polarizer opposite to the easy-adhesion layer. As the forming material of the above-mentioned protective film, for example, cellulose resins such as (meth) acrylic resins, cellulose diacetate, cellulose triacetate, olefin resins such as cycloolefin resins, polypropylene, ester resins such as polyethylene terephthalate resins, polyamide resins, polycarbonate resins, and their copolymer resins can be cited. The thickness of the protective film is preferably 10μm to 100μm.

[0073] D. Method for manufacturing polarizing film

[0074] The method for manufacturing a polarizing plate of the present invention comprises: dyeing and stretching the laminate described in the above-mentioned item A, thereby making the PVA-based resin layer into a polarizer. In one embodiment, it may include: subjecting the laminate to various treatments such as dyeing, stretching, insolubilization, crosslinking, cleaning, and drying. These treatments can be appropriately selected according to the purpose. In addition, the treatment sequence, treatment period, number of treatments, etc. can be appropriately set. Each treatment is described below.

[0075] D-1. Stretching in gas atmosphere

[0076] The stretching method for auxiliary stretching in a gas atmosphere may be fixed-end stretching (e.g., a method of stretching using a tenter stretching machine) or free-end stretching (e.g., a method of unidirectional stretching by passing the laminate between rollers of different circumferential speeds). In one embodiment, the stretching treatment in a gas atmosphere includes a hot roller stretching step, which stretches the laminate by the circumferential speed difference between the hot rollers while conveying the laminate along its long side. The stretching treatment in a gas atmosphere typically includes a zone stretching step and a hot roller stretching step. It should be noted that the order of the zone stretching step and the hot roller stretching step is not limited, and the zone stretching step may be performed first, or the hot roller stretching step may be performed first. The zone stretching step may also be omitted. In one embodiment, the zone stretching step and the hot roller stretching step are performed in sequence.

[0077] The stretching temperature of the laminate can be set to any appropriate value according to the forming material of the resin substrate, etc. The stretching temperature during the stretching treatment in the gas atmosphere is preferably above the glass transition temperature (Tg) of the resin substrate, more preferably above the glass transition temperature (Tg) of the resin substrate + 10°C, and particularly preferably above Tg + 15°C. On the other hand, the upper limit of the stretching temperature of the laminate is preferably 170°C. Stretching at such a temperature can inhibit the rapid progress of crystallization of the PVA-type resin, thereby inhibiting the adverse conditions caused by the crystallization (for example, hindering the orientation of the PVA-type resin layer due to stretching).

[0078] The stretching ratio of the laminate can be set to any appropriate value depending on the material forming the resin substrate, etc. The stretching ratio of the in-atmosphere stretching treatment is preferably 1.5 times or more and 3.0 times or less.

[0079] D-2. Insolubilization treatment

[0080] The above-mentioned insolubilization treatment is typically carried out by immersing the PVA type resin layer in a boric acid aqueous solution. By implementing the insolubilization treatment, water resistance can be imparted to the PVA type resin layer. The concentration of the boric acid aqueous solution is preferably 1 weight part to 4 weight parts relative to 100 weight parts of water. The liquid temperature of the insolubilization bath (boric acid aqueous solution) is preferably 20°C to 50°C. The insolubilization treatment is preferably carried out in an aqueous solution before stretching and dyeing.

[0081] D-3. Dyeing treatment

[0082] The dyeing treatment is typically performed by dyeing the PVA type resin layer with a dichroic substance. It is preferably performed by adsorbing the dichroic substance on the PVA type resin layer. The adsorption method may include, for example, a method of immersing the PVA type resin layer (laminated body) in a dyeing solution containing a dichroic substance, a method of applying the dyeing solution on the PVA type resin layer, a method of spraying the dyeing solution on the PVA type resin layer, etc. It is preferred to immerse the laminate in the dyeing solution. This is because the dichroic substance can be adsorbed well.

[0083] As the above-mentioned dichroic substance, for example, iodine and organic dyes can be mentioned. They can be used alone or in combination of two or more. The dichroic substance is preferably iodine. When iodine is used as the dichroic substance, the above-mentioned dyeing solution is preferably an iodine aqueous solution. The amount of iodine is preferably 0.05 weight part to 5.0 weight parts relative to 100 weight parts of water. In order to improve the solubility of iodine in water, it is preferred to add iodide to the iodine aqueous solution. As iodide, for example: potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, titanium iodide, etc. can be mentioned. Potassium iodide is preferred among these. The amount of iodide is preferably 0.3 weight part to 15 weight parts relative to 100 weight parts of water.

[0084] The liquid temperature of the dyeing solution during dyeing is preferably 20°C to 40°C. When the PVA-type resin layer is immersed in the dyeing solution, the immersion time is preferably 10 seconds to 300 seconds. Under such conditions, the dichroic substance can be fully adsorbed on the PVA-type resin layer. In addition, the dyeing conditions (concentration, liquid temperature, immersion time) can be set in a manner that the polarization degree or monomer transmittance of the polarizer finally obtained is within a given range. In one embodiment, the immersion time is set in a manner that the polarization degree of the obtained polarizer is greater than 99.98%. In another embodiment, the immersion time is set in a manner that the monomer transmittance of the obtained polarizer is about 40%.

[0085] D-4. Cross-linking treatment

[0086] The above-mentioned cross-linking treatment is typically carried out by immersing the PVA-type resin layer (laminate) in an aqueous solution of boric acid. By implementing the cross-linking treatment, water resistance can be imparted to the PVA-type resin layer. The concentration of the aqueous solution of boric acid is preferably 1 to 5 parts by weight relative to 100 parts by weight of water. In addition, when the cross-linking treatment is carried out after the above-mentioned dyeing treatment, it is preferably further combined with an iodide. By combining an iodide, the dissolution of iodine adsorbed on the PVA-type resin layer can be suppressed. The amount of iodide combined is preferably 1 to 5 parts by weight relative to 100 parts by weight of water. Specific examples of iodide are as described above. The liquid temperature of the cross-linking bath (boric acid aqueous solution) is preferably 20°C to 60°C. The cross-linking treatment is preferably carried out before the stretching treatment in the aqueous solution. In a preferred embodiment, the stretching treatment, dyeing treatment and cross-linking treatment in a gas atmosphere are carried out in sequence.

[0087] D-5. Stretching treatment in aqueous solution

[0088] As a stretching method for stretching treatment in aqueous solution, any appropriate method can be used. Specifically, it can be fixed-end stretching (for example, a method using a tenter stretching machine), or it can be free-end stretching (for example, a method of uniaxially stretching the laminate by passing it between rollers of different circumferential speeds). In addition, it can be synchronous biaxial stretching (for example, a method using a synchronous biaxial stretching machine) or it can be stepwise biaxial stretching. The stretching of the laminate can be carried out in one stage or in multiple stages. When it is carried out in multiple stages, the stretching ratio (maximum stretching ratio) of the laminate is the product of the stretching ratios of each stage.

[0089] The stretching direction of the laminate can be any appropriate direction. In one embodiment, the laminate is stretched along the long side direction of the long laminate. Specifically, the laminate is transported along the long side direction, which is the transport direction (MD). In another embodiment, the laminate is stretched along the width direction of the long laminate. Specifically, the laminate is transported along the long side direction, which is the direction (TD) orthogonal to the transport direction (MD).

[0090] The stretching temperature of the laminate can be set to any appropriate value according to the forming material of the resin substrate, the stretching method, etc. The stretching temperature is preferably 40°C to 85°C, and more preferably 50°C to 85°C. As long as it is within the temperature, the dissolution of the PVA-type resin layer can be suppressed, and it can be stretched at a high ratio. Specifically, as described above, considering the relationship with the formation of the PVA-type resin layer, the glass transition temperature (Tg) of the resin substrate is preferably above 60°C. At this time, if the stretching temperature is lower than 40°C, there is a concern that even if the resin substrate is plasticized with water, it cannot be stretched well. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-type resin layer, and there is a concern that excellent optical properties cannot be obtained.

[0091] Stretching in aqueous solution is preferably performed by immersing the laminate in an aqueous solution of boric acid (stretching in aqueous solution of boric acid). By using an aqueous solution of boric acid as a stretching bath, the PVA-based resin layer can be given rigidity that can withstand the tension applied during stretching and water resistance that is insoluble in water. Specifically, boric acid generates tetrahydroxyborate anions in an aqueous solution, which cross-link with the PVA-based resin through hydrogen bonds. As a result, the PVA-based resin layer can be given rigidity and water resistance, and can be stretched well, and a polarizer with excellent optical properties (such as polarization degree) can be produced.

[0092] The boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, the dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizer with higher characteristics can be manufactured. In addition to boric acid or a borate, an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, etc. in a solvent can also be used.

[0093] When the dichroic substance (represented by iodine) is adsorbed on the PVA resin layer by dyeing treatment in advance, it is preferred to add an iodide in the above-mentioned stretching bath (boric acid aqueous solution). By adding an iodide, the dissolution of iodine adsorbed on the PVA resin layer can be suppressed. As iodide, for example: potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, titanium iodide, etc. can be cited. Potassium iodide is preferred among these. The concentration of iodide is preferably 0.05 to 15 parts by weight relative to 100 parts by weight of water, and more preferably 0.5 to 8 parts by weight.

[0094] The stretching ratio (maximum stretching ratio) of the laminate is representatively 4.0 times or more, preferably 5.0 times or more, relative to the original length of the laminate. Such a high stretching ratio can be achieved by, for example, stretching in an aqueous solution (stretching in a boric acid aqueous solution). It should be noted that in this specification, "maximum stretching ratio" refers to the stretching ratio before the laminate is about to break, which is a value 0.2 lower than the stretching ratio at which the laminate is broken.

[0095] The aqueous solution stretching treatment is preferably performed after the dyeing treatment.

[0096] D-6. Cleaning

[0097] The above-mentioned cleaning treatment can be typically performed by immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0098] D-7. Drying treatment

[0099] The drying temperature in the drying treatment is preferably 30°C to 100°C.

[0100] Example

[0101] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. It should be noted that the measuring method and the evaluation method of each characteristic are as follows.

[0102] (1) Thickness

[0103] The measurement was performed using a digital micrometer (manufactured by Anritsu Corporation, product name "KC-351C").

[0104] (2) Water contact angle

[0105] The water contact angle of the easy-adhesion layer was measured using an automatic contact angle meter (DM500) manufactured by Kyowa Interface Science Co., Ltd. and analyzed using FAMAS (contact angle measurement plug-in). Ultrapure water was used for the measurement, and the droplet size was 0.5 μl.

[0106] After forming an easy-adhesive layer on the surface of the polyester resin substrate, the water contact angle (θ1) 1 second after water was dropped onto the easy-adhesive layer and the water contact angle (θ2) 30 seconds after the drop were measured, and the change in the water contact angle over time after 30 seconds (θ2-θ1) was calculated.

[0107] <Example 1>

[0108] 1. Preparation of laminated body

[0109] As the polyester resin substrate, a long amorphous isophthalic acid copolymer polyethylene terephthalate (IPA copolymer PET) film (thickness: 100 μm) having a water absorption rate of 0.75% and a Tg of 75° C. was used.

[0110] A single side of a polyester resin substrate is subjected to corona treatment, and a mixed solution (solid content concentration of 4.0%) is applied to the corona treated surface in a manner such that the thickness after drying becomes 2000 nm, and then dried at 60°C for 3 minutes to form an easy-adhesive layer. The mixed solution is a 4.0% aqueous solution of acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z200", degree of polymerization 1200, saponification degree 99.0 mol% or more, acetoacetyl modification degree 4.6%), a modified polyolefin resin aqueous dispersant (manufactured by Unitika, trade name "ARROW BASE SE1030N", solid content concentration 22%), and pure water. Here, the solid content ratio of acetoacetyl-modified PVA to modified polyolefin in the mixed solution is 50:50.

[0111] Then, the surface of the easy-adhesive layer was subjected to corona treatment, and an aqueous solution containing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol %) and acetoacetyl-modified PVA (polymerization degree 1200, acetoacetyl modification degree 4.6%, saponification degree 99.0 mol % or more, manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z200") in a ratio of 9:1 was applied to the corona-treated surface and dried to form a PVA-based resin layer having a thickness of 11 μm. A laminate was manufactured as described above.

[0112] 2. Production of polarizing filter

[0113] The obtained laminate was subjected to free-end uniaxial stretching by 2.0 times in the longitudinal direction (longitudinal direction) between rolls of different peripheral speeds in an oven at 120° C. (auxiliary stretching in a gas atmosphere).

[0114] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 30° C. for 30 seconds (insolubilization treatment).

[0115] Next, the polarizer is immersed in a dyeing bath at a liquid temperature of 30° C. and the iodine concentration and immersion time are adjusted so that the polarizer reaches a given transmittance. In this embodiment, the polarizer is immersed in an iodine aqueous solution obtained by mixing 0.2 parts by weight of iodine and 1.0 parts by weight of potassium iodide with respect to 100 parts by weight of water for 60 seconds (dyeing treatment).

[0116] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 3 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 30° C. for 30 seconds (crosslinking treatment).

[0117] Thereafter, the laminate was immersed in an aqueous boric acid solution at a liquid temperature of 70°C (an aqueous solution obtained by mixing 4 parts by weight of boric acid and 5 parts by weight of potassium iodide with respect to 100 parts by weight of water), and was uniaxially stretched in the longitudinal direction (long side direction) between rollers of different circumferential speeds so that the total stretching ratio became 5.5 times (stretching in aqueous solution).

[0118] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 30° C. (cleaning treatment).

[0119] In this way, a polarizing plate in which a polarizer having a thickness of 5 μm was formed on one side of a polyester resin substrate having a thickness of 30 μm was obtained.

[0120] <Example 2>

[0121] A polarizing plate was obtained in the same manner as in Example 1 except that the solid content ratio of the acetoacetyl-modified PVA to the modified polyolefin in the mixed liquid was 30:70.

[0122] <Example 3>

[0123] A polarizing plate was obtained in the same manner as in Example 1 except that the solid content ratio of the acetoacetyl-modified PVA to the modified polyolefin in the mixed liquid was 20:80.

[0124] <Example 4>

[0125] A polarizing plate was obtained in the same manner as in Example 1 except that the solid content ratio of the acetoacetyl-modified PVA to the modified polyolefin in the mixed liquid was 10:90.

[0126] <Comparative Example 1>

[0127] A polarizing plate was obtained in the same manner as in Example 1 except that a 4.0% aqueous solution of acetoacetyl-modified PVA (GOHSEFIMER Z200) was used when forming the easy-adhesion layer.

[0128] <Comparative Example 2>

[0129] A polarizing plate was obtained in the same manner as in Example 1 except that the solid content ratio of the acetoacetyl-modified PVA to the modified polyolefin in the mixed liquid was 90:10.

[0130] <Comparative Example 3>

[0131] A polarizing plate was obtained in the same manner as in Example 1 except that the solid content ratio of the acetoacetyl-modified PVA and the modified polyolefin in the mixed liquid was 70:30.

[0132] <Comparative Example 4>

[0133] A polarizing plate was obtained in the same manner as in Example 3 except that a mixed solution (solid content concentration 4.0%) of a modified polyolefin resin aqueous dispersion (Unitika Co., Ltd., trade name “ARROW BASE SE1030N”, solid content concentration 22%) and pure water was used to form the easy-adhesion layer.

[0134] (evaluate)

[0135] The adhesion of the above-mentioned Examples and Comparative Examples was evaluated by measuring the PVA peeling force and the substrate peeling force. The evaluation results are summarized in Table 1. The methods for measuring the PVA peeling force and the substrate peeling force are as follows.

[0136] (PVA peeling force)

[0137] After applying adhesive to the polyester resin substrate side, the obtained polarizer was bonded to a glass plate, and a reinforcing polyimide tape (manufactured by Nitto Denko Co., Ltd., polyimide adhesive tape No. 360A) was bonded to the polarizer surface to prepare a measurement sample. After a cut was made between the polarizer and the polyester resin substrate of the measurement sample with a cutter, the force (N / 15mm) required when the polarizer and the reinforcing polyimide tape were picked up at an angle of 90° relative to the polyester resin substrate surface and peeled off at a peeling speed of 3000mm / min was measured using an angle-variable adhesion / film peeling analysis device "VPA-2" (manufactured by Kyowa Interface Chemical Co., Ltd.).

[0138] (Substrate peeling force)

[0139] After applying adhesive on the polarizer side, the obtained polarizing plate was bonded to a glass plate to prepare a sample for measurement. After cutting a cut between the polarizer and the polyester resin substrate of the sample for measurement with a cutting knife, the force (N / 15mm) required to peel off the polyester resin substrate at an angle of 90° relative to the polarizer surface at a peeling speed of 3000mm / min was measured using the above-mentioned "VPA-2".

[0140]

[0141] It is clear from Table 1 that the water contact angle of the easy bonding layer of the polarizing plate of Examples 1 to 4 is 70° or more immediately after water is dropped, and the water cross-entanglement angle of the easy bonding layer decreases by 2° or more 30 seconds after the drop, so the polarizer and the polyester resin substrate have excellent adhesion.

[0142] Industrial Applicability

[0143] The laminate of the present invention can be suitably used for the production of a polarizing plate. The polarizing plate of the present invention can be suitably used for image display devices such as a liquid crystal display device and an organic EL display device.

Claims

1. A laminate comprising a polyester resin substrate having an easy-adhesion layer formed on the surface thereof, and a polyvinyl alcohol resin layer laminated on the polyester resin substrate via the easy-adhesion layer, The easy-adhesion layer contains a polyvinyl alcohol component and a polyolefin component in a mixing ratio of 10:90 to 50:50, wherein the polyvinyl alcohol component includes acetoacetyl-modified polyvinyl alcohol. The water contact angle of the easy-adhesion layer is 70° or more immediately after water is dropped onto the easy-adhesion layer, and decreases by 2° or more after 30 seconds have passed since the dropping.

2. A method for manufacturing a laminate, the method comprising: Forming an easy-adhesive layer on the surface of a polyester resin substrate; as well as forming a polyvinyl alcohol resin layer on the surface of the easy-adhesion layer, The easy-adhesion layer contains a polyvinyl alcohol component and a polyolefin component in a mixing ratio of 10:90 to 50:50, wherein the polyvinyl alcohol component includes acetoacetyl-modified polyvinyl alcohol. The water contact angle of the easy-adhesion layer is 70° or more immediately after water is dropped onto the easy-adhesion layer, and decreases by 2° or more after 30 seconds have passed since the dropping.

3. A method for manufacturing a polarizing plate, the method comprising: The laminate according to claim 1 is dyed and stretched, whereby the polyvinyl alcohol-based resin layer is made into a polarizer.

4. A polarizing plate comprising a polyester resin substrate having an easy-adhesion layer formed on the surface thereof, and a polarizer laminated on the polyester resin substrate via the easy-adhesion layer. The thickness of the polarizer is less than 10 μm, The easy-adhesion layer contains a polyvinyl alcohol component and a polyolefin component in a mixing ratio of 10:90 to 50:50, wherein the polyvinyl alcohol component includes acetoacetyl-modified polyvinyl alcohol. The water contact angle of the easy-adhesion layer is 70° or more immediately after water is dropped onto the easy-adhesion layer, and decreases by 2° or more after 30 seconds have passed since the dropping.

Citation Information

Patent Citations

  • Polarizing plate and its production

    JP2000338329A